2020
DOI: 10.1371/journal.pmed.1003434
|View full text |Cite
|
Sign up to set email alerts
|

Health system interventions for adults with type 2 diabetes in low- and middle-income countries: A systematic review and meta-analysis

Abstract: Background Effective health system interventions may help address the disproportionate burden of diabetes in low- and middle-income countries (LMICs). We assessed the impact of health system interventions to improve outcomes for adults with type 2 diabetes in LMICs. Methods and findings We searched Ovid MEDLINE, Cochrane Library, EMBASE, African Index Medicus, LILACS, and Global Index Medicus from inception of each database through February 24, 2020. We included randomized controlled trials (RCTs) of health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 78 publications
(171 reference statements)
1
17
0
1
Order By: Relevance
“…Studies have shown that delivery of diabetes care through strong PHC has resulted in lower health costs, better health outcomes, higher satisfaction of people with diabetes, fewer hospitalization rate, and greater socioeconomic equity (32)(33)(34)(35). While the prevalence of diabetes and its impact on health and overall quality of life is high in Nepal, low institutional capacity of primary health care center, inadequate human resources for health, lack of resources/funding and priority for diabetes and other NCDs and poor intersectoral coordination are some key challenges to implementing programs for prevention and control of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that delivery of diabetes care through strong PHC has resulted in lower health costs, better health outcomes, higher satisfaction of people with diabetes, fewer hospitalization rate, and greater socioeconomic equity (32)(33)(34)(35). While the prevalence of diabetes and its impact on health and overall quality of life is high in Nepal, low institutional capacity of primary health care center, inadequate human resources for health, lack of resources/funding and priority for diabetes and other NCDs and poor intersectoral coordination are some key challenges to implementing programs for prevention and control of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…When compared to a control group, these reviews, exploring self-management education [ 11 ] in the Asian Western Pacific region, diet/exercise modification [ 12 ] in a Southeast Asian population and a combination of both (primarily in high-income countries) [ 54 ], reported a significant reduction in HbA1c and BMI from the baseline in the lifestyle intervention groups. Specifically with regard to LMICs, a very recent review exploring health system interventions for adults with T2DM with similar cohort selection criteria to ours found diabetes multicomponent self-management education interventions to be successful at improving glycemic control [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings showed that programs delivered by HCPs in a clinical environment were more effective in reducing HbA1c than those delivered by peer educators at home or in a community setting. Previous reviews have reported on the differences between interventions that are delivered by one healthcare professional versus a multidisciplinary team [ 11 , 55 ], showing a team approach to be more effective. A very recent review exploring the effectiveness of peer- and community health worker-led self-management education programs in LMICs showed inconsistent improvements in clinical, behavior and psychological outcomes [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…About one-third of diabetic patients develop DR and about one-third of patients with DR develop DME ( 58 ). Until now, diabetes mellitus (DM) remains a major health burden, with ~80% occurring in low- and middle-income countries ( 59 , 60 ). The number of DM in China is expected to increase to 142.7 million by 2035 ( 61 ).…”
Section: Discussionmentioning
confidence: 99%